2018
DOI: 10.1055/s-0038-1636916
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection in a Tertiary Neonatal Surgery Centre

Abstract: This is the first article benchmarking the incidence of SSI in neonatal surgery in the United Kingdom. A preoperative stay ≥4 days and gastrointestinal procedures were independent risk factors for SSI. More research is needed to develop strategies to reduce SSI in selected neonatal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
(28 reference statements)
1
15
0
4
Order By: Relevance
“…We analyzed 10 comparative studies (Tables 2a,b) (1618, 22, 24, 34, 45, 47, 51, 60). Among these articles, there were only two prospective cohort studies (45, 60) and one national prospective database (16). No randomized studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed 10 comparative studies (Tables 2a,b) (1618, 22, 24, 34, 45, 47, 51, 60). Among these articles, there were only two prospective cohort studies (45, 60) and one national prospective database (16). No randomized studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of the 10 comparative studies (1618, 22, 24, 34, 45, 47, 51, 60) showed that there was a slight albeit significant difference between neonates with and without SSI for gestational age (34.2 ± 2.4 weeks vs. 34.7 ± 2.3; p < 0.00001, MD −1.02, 95% CI [−1.22, −0.82], I 2 = 86%; Figure 2) and birth weight (2,171 ± 479 grams vs. 2,384 ± 411; p < 0.00001, MD −0.29, 95% CI [−0.35, −0.23], I 2 = 86%; Figure 3). Neonates with SSI were older at surgery compared to those without SSI (28.4 ± 24.4 days vs. 16.7 ± 14.3; p < 0.00001, MD 3.24, 95% CI [2.55, 3.93], I 2 = 98%; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…17 Factors associated with an increased risk of SSI include; emergency procedures and longer duration of surgery. 18 Numerous risk factors are involved in SSI with a complex relationship as; surgery, patients, microbial, and environmentrelated factors. 18 The incidence rate of SSIs mainly depends upon the health care facility, surgical procedure, and level of care.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of adverse events in the population of hospitalized Canadian children have been measured at close to 10% with the highest rates seen in surgical patients [16]. Neonates are at particularly high risk with rates of surgical site infections reported as high as 13.5% [17,18]. The morbidity associated with these infections is reflected in a length of stay for these infants that is three times longer than the stay of their uninfected counterparts [17].…”
mentioning
confidence: 99%
“…Neonates are at particularly high risk with rates of surgical site infections reported as high as 13.5% [17,18]. The morbidity associated with these infections is reflected in a length of stay for these infants that is three times longer than the stay of their uninfected counterparts [17].…”
mentioning
confidence: 99%